Pandangan terhadap Orang Asing: Tinjauan Baumanian-Levinasian atas Agama di Tengah Krisis Pengungsi - Kevin Nobel Kurniawan (Reformed Center for Religion and Society, 2023)
This article discusses the relevance of the Baumanian-Levinasian notion of religion within a concrete analysis of refugee reception. As various classical approaches and definitions of religion have described it as a social phenomenon of grouping or an ideological tool for maintaining social order, it is necessary to provide a relevant approach to discussing religion as an ethical drive to build social inclusion through transmigration. The previous 2015 Western Europe immigration crisis due to the Syrian civil war has invited xenophobic responses towards immigrants, inevitably resulting in the socio-political impact of Brexit in 2020. Demonstrations of refugee resettlement driven by religious causes have provided a practical and ethical critique of secular liberalism. Furthermore, this article also reflects on the church's role as a refuge for refugees and marginalised groups in Indonesia. In conclusion, the Baumanian-Levinasian thought on religion and ethics remains relevant to both Western and Indonesian contexts in fostering inclusion, particularly during political turmoil.